Identification of nitric oxide inhibitory compounds from the rhizome of Curcuma xanthorrhiza - Awin, Tahani M.; Buzgaia, Nawal; Abd Ghafar, Siti Zulaikha; Mediani, Ahmed; Mohd Zaudzi, Siti Munirah; Maulidiani, M.; Shaari, Khozirah; Abas, Faridah (Elsevier BV, 2019)
Curcuma xanthorrhiza is a natural source of traditional medicines with numerous biological properties. This study profiles the metabolites in different fractions (hexane, chloroform, ethyl acetate and methanol) of the ethanolic extracts of C. xanthorrhiza using a nuclear magnetic resonance-based metabolomics approach. The nitric oxide (NO) inhibitory activity was determined using a Griess assay. The bioactivity and phytochemical constituents were correlated using partial least squares regression that indicated the differences between the 4 solvents based on the identified metabolites and their bioactivities. The results showed that the ethyl acetate fractions of C. xanthorrhiza had the highest NO inhibitory activity, this high activity is associated with the large quantity of curcuminoids found in this fraction. The metabolites that are responsible for the bioactivity are curcumin, demethoxycurcumin, l-hydroxy-1,7-bis(4-hydroxy-3-methoxyphenyl)-6-heptene-3,5-dione, and 1-(4- hydroxy-3,5-dimethoxyphenyl)-7-(4-hydroxy-3-methoxyphenyl)-1,6-heptadiene-3,5-dione. Ultra-performance liquid chromatography–tandem mass spectrometry was used to identify more metabolites in the active fraction, including bisdemethoxycurcumin and 1,7-bis(4-hydroxy-3-methoxyphenyl)-heptane-3,5-diol. The findings suggested that the ethyl acetate fraction of C. xanthorrhiza showed significant activity and can be a potential natural source of NO inhibitors.